2022
DOI: 10.1172/jci152187
|View full text |Cite|
|
Sign up to set email alerts
|

The Eph receptor A4 plays a role in demyelination and depression-related behavior

Abstract: Proper myelination of axons is crucial for normal sensory, motor and cognitive function. Abnormal myelination is seen in brain disorders such as major depressive disorder (MDD), but the molecular mechanisms connecting demyelination with the pathobiology remain largely unknown. We observed demyelination and synaptic deficits in mice exposed to either chronic unpredictable mild stress (CUMS) or lipopolysaccharide (LPS), two paradigms for inducing depression-like states.Pharmacologically restoring myelination nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Growing evidence has implicated neuroin ammationinduced demyelination as an important pathological features in major depressive disorder (MDD) and multiple sclerosis (MS), and myelin de cits contribute to mood swing and cognitive decline. 17,18,33 Our results using FluoroMyelin Green uorescent myelin staining, electron microscopy, immunohistochemistry, and western blotting demonstrated that deletion of ADAM10 in OPCs caused signi cant premyelination on P30 but demyelination on P60. In further studies, we found that conditional deletion of ADAM10 in OPCs interfered with the development of OPCs and decreased OPC proliferation in ADAM10 cKO mice.…”
Section: Discussionmentioning
confidence: 76%
“…Growing evidence has implicated neuroin ammationinduced demyelination as an important pathological features in major depressive disorder (MDD) and multiple sclerosis (MS), and myelin de cits contribute to mood swing and cognitive decline. 17,18,33 Our results using FluoroMyelin Green uorescent myelin staining, electron microscopy, immunohistochemistry, and western blotting demonstrated that deletion of ADAM10 in OPCs caused signi cant premyelination on P30 but demyelination on P60. In further studies, we found that conditional deletion of ADAM10 in OPCs interfered with the development of OPCs and decreased OPC proliferation in ADAM10 cKO mice.…”
Section: Discussionmentioning
confidence: 76%
“…Using the chronic, unpredictable mild stress (CUMS) exposure or lipopolysaccharide (LPS) administrationinduced animal model of depression, the authors first analyzed the association between depression and demyelination. They conducted the three most commonly used behavioral tests for depression and found depressive-like behavior in the CUMS and LPS-induced depression models [1]. Moreover, the myelin basic protein (MBP) staining and the luxor fast blue (LFB) staining demonstrated a significantly decreased myelination in the depressive animal models, which was also confirmed by Western blotting.…”
mentioning
confidence: 88%
“…Major depressive disorder (MDD), also known as clinical depression or depression, is one of the most common mental illnesses. It is characterized by pervasive and persistent low mood, disturbed memory, concentration, sleep, low motivation, and a loss of interest in enjoyable activities [1,2]. Evidence from genetic, neuroimaging, nonhuman animals and post-mortem has suggested abnormal myelination in the MDD [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations